Climate Smart Agriculture Rapid Appraisal (CSA-RA): a prioritization tool for outscaling. Step-by-step guidelines. - Mwongera, Caroline; Twyman, Jennifer; Shikuku, Kelvin Mashisia; Winowiecki, Leigh Ann; Okolo, Wendy; Läderach, Peter R.D.; Ampaire, Edidah L.; Asten, Piet J.A. van; Twomlow, Stephen (2014)
Climate Smart Agriculture Rapid Appraisal (CSA-RA) is a prioritization tool for outscaling Climate Smart Agriculture. This manual provides step-by-step guidelines in implementing the CSA-RA. This process provides an assessment of key barriers and opportunities to CSA adoption across landscapes by collecting gender-disaggregated data, perceptions of climate variability, resource and labour allocation, as well as economic assessments at the household level. The approach combines participatory workshops, expert interviews, household/farmer interviews, and farm transect walks to gather and capture the realities and challenges facing diverse farming communities.